Targeting epimastigotes of trypanosoma cruzi with a peptide isolated from a phage display random library (2020)
Chagas disease, also known as American trypanosomiasis, is a potentially life-threatening illness caused by the protozoan parasite Trypanosoma cruzi, which is transmitted by insects of the family Reduviidae. Since conventional treatments with nitroheterocyclic drugs show serious adverse reactions and have questionable efficiency, different research groups have investigated polypeptide-based approaches to interfere with the parasite cell cycle in other Trypanosomatids. These strategies are supported by the fact that surface players are candidates to develop surface ligands that impair function since they may act as virulence factors. In this study, we used a phage display approach to identify peptides from one library-LX8CX8 (17 aa) (where X corresponds to any amino acid). After testing different biopanning conditions using live or fixed epimastigotes, 10 clones were sequenced that encoded the same peptide, named here as EPI18. The bacteriophage expressing EPI18 binds to epimastigotes from distinct strains of T. cruzi. To confirm these results, this peptide was synthetized, biotinylated, and assayed using flow cytometry and confocal microscopy analyses. These assays confirmed the specificity of the binding capacity of EPI18 toward epimastigote surfaces. Our findings suggest that EPI18 may have potential biotechnological applications that include peptide-based strategies to control parasite transmission.